Design and fabrication of knife sharpener / Wan Iqmal Nur’iman A’zali - A’zali, Wan Iqmal Nur’iman (2024)
Sharpening a knife nowadays can be a difficult and time-consuming task. People are currently employing the old way, such as slicing the blade with the sharpener stone. This conventional method necessitates a cyclic movement of the hand with added pressure. This action requires a lot of energy from the user all the time. The continual cyclic procedure occasionally resulted in damage to the user. Aside from that, users have difficulty determining whether the knife is sharp enough. Because of the problems mentioned, the goal of this project is to address all of them. This project will concentrate on developing a product that will ease the process, reduce the danger of injuries, and ensure that the knife is sharp enough after the sharpening process. Data from the user will be collected and analyzed in this project. The information gathered will be used to build the Product Design Specification (PDS). In terms of selecting the conceptual design, I used a Pugh chart to compare the concept designs generated based on several parameters. Each design will be rated based on numerous criteria, and the total number of points earned will determine the best design for this project. The chosen concept design will then be produced in Solidworks to be utilized as the final design. Later, the SolidWork analysis was used to the final design to forecast the product's real-world behaviour. Following this was the most essential step, fabrication, which is where the product production process takes place. Finally, the finished product must be tested to ensure that everything works as it should. It is expected that the device will be strong and safe, and that it will effectively assist the user in sharpening